We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.

How to solve this problem?


 Jul 30, 2017
edited by BOSEOK  Aug 9, 2017

Do you mean \(2-x-2=4\)?


If so, I will solve it as so:

\(2-x-2=4\) Combine the like terms on the left hand side of the equation
\(-x=4\) Divide by -1 on both sides to get rid of the negative on the x.


If you are ever unsure if you have the correct value for your unknown, just plug it back into the equation:


\(2-(-4)-2=4\) Check to see if this is true; if it is wrong, you either made a mistake or you have an extraneous solution.
\(2+4-2=4\) Subtracting a negative number is the equivalent of adding a positive one.
\(4=4\) 4=4 is a true statement and concludes that the value for x is correct.
 Jul 30, 2017

8 Online Users